KNOWLEDGE ABOUT DENTAL HYGIENE MAINTENANCE AND THE MOUTH OF THE TEENAGE STUDENTS OF THE Islamic Boarding School AL IKHLAS PURBOYO SIDOARJO DISTRICT: PENGETAHUAN TENTANG PEMELIHARAAN KEBERSIHAN GIGI DAN MULUT SANTRI REMAJA PONDOK PESANTREN AL IKHLAS PURBOYO KABUPATEN SIDOARJO - SALSABILLA FIRDAUS; Isnanto; Sri Hidayati (SURABAYA DENTAL THERAPIST JOURNAL, 2024)
Dental and oral health problems are an important concern health development, one of which is caused by vulnerable groups school age children from dental health problems. School age is an age important in the growth and physical development of children. This period is also called as a critical period because at this time children begin to develop habits which usually tends to persist into adulthood. One of them is habit maintain dental and oral hygiene. Behavior of Indonesian children in caring oral health is still low. The problem with this study is the high scores OHI-S in teenage students at the Al Ikhlas Islamic Boarding School, Purboyo Regency Sidaorjo. The aim of this research is to gain knowledge about maintenance of oral hygiene of teenage students at the Al Ikhlas Islamic Boarding School Purboyo, Sidaorjo Regency. This research method is descriptive research. The target of this research is teenage students at the Al Ikhlas Islamic Boarding School Purboyo, Sidoarjo Regency, as many as 25 children. Instruments used in This research is in the form of a questionnaire. Data analysis techniques used in This research involves calculating the amount of data from a questionnaire and then creating it averages in the form of frequency distributions and percentages and are presented in table form. The research results show that knowledge about Dental and oral hygiene in adolescent students at the Al Ikhlas Purboyo Islamic Boarding School Sidoarjo Regency is in the deficient criteria. Keyword : knowledge; dental and oral hygiene; OHI-S; teenager